The Influence of Brand Awareness, Brand Image, and Brand Trust on Purchase Intention of Excelso Coffee in Malang City - Mohammad Adhyaksa Auliya’ul Hakim; Peter Remy Yosy Pasla (PT FORMOSA CENDEKIA GLOBAL, 2024)
Considering how fiercely competitive the coffee and cafe industries are, it is critical for businesses to use effective strategies to increase consumer intent to purchase. One of the largest coffee brands in Indonesia is Excelso Coffee. The purpose of this study is to determine how consumer intentions to buy Excelso Coffee in Malang City are influenced by brand awareness, brand image, and brand trust. This research employs a quantitative approach using a questionnaire disseminated via Google Forms. The 100 respondents in the sample are analyzed using the SPSS program. Conventional assumption tests such the linearity, homoscedasticity, non-multicollinearity, and normality tests were employed in this investigation. The outcomes of the traditional assumption tests show that the variables of brand awareness, brand image, and brand trust all have a positive simultaneous influence on Excelso Coffee's desire to purchase.